2022
DOI: 10.1093/stmcls/sxac031
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a Promotes AT1 and Represses AT2 Lineage-Specific Gene Expression in a Cell-Context-Dependent Manner

Abstract: Lung maturation is not limited to proper structural development, but also includes differentiation and functionality of various highly specialized alveolar cell types. Alveolar type 1 cells (AT1s) occupy nearly 95% of the alveolar surface and are critical for establishing efficient gas exchange in the mature lung. AT1 cells arise from progenitors specified during the embryonic stage as well as alveolar epithelial progenitors expressing surfactant protein C (Sftpc pos cells) during postnatal and adult stages. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
11
1
Order By: Relevance
“…In mice induced after H1N1 injury, however, the percentage of Atf3-positive pulmonary ECs in the distal lung was dramatically increased ( Figure 2C ). Although Atf3 expression has been reported in proliferating AT2 cells in mice infected with Streptococcus pneumoniae (Ali et al, 2022), we did not observe an increase in Atf3-positive AT2 cells or in Atf3-positive mesenchymal cells following influenza infection ( Figure 2 – S2A-B ). Our data also show that the increase in Atf3-expressing (CD45 - /tdTm + ) cells that we observed after H1N1 was specific to the endothelial compartment, and a similar increase did not occur in CD31 - non-ECs ( Figure 2C, Figure 2 – S2C-D ).…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…In mice induced after H1N1 injury, however, the percentage of Atf3-positive pulmonary ECs in the distal lung was dramatically increased ( Figure 2C ). Although Atf3 expression has been reported in proliferating AT2 cells in mice infected with Streptococcus pneumoniae (Ali et al, 2022), we did not observe an increase in Atf3-positive AT2 cells or in Atf3-positive mesenchymal cells following influenza infection ( Figure 2 – S2A-B ). Our data also show that the increase in Atf3-expressing (CD45 - /tdTm + ) cells that we observed after H1N1 was specific to the endothelial compartment, and a similar increase did not occur in CD31 - non-ECs ( Figure 2C, Figure 2 – S2C-D ).…”
Section: Resultscontrasting
confidence: 71%
“…Temporal changes in TF expression may also alter the choice to proliferate or differentiate within a certain cell population. Specific TFs also differentially regulate activation of signaling pathways in the lung known to affect progenitor function, including Wnt signaling (Barkauskas et al, 2013; Frank et al, 2016; Li et al, 2022; Liberti et al, 2021; Nabhan et al, 2018; Wang et al, 2016; Zacharias et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…PDGFRA + fibroblasts support alveolar type 2 (AT2) and alveolar type 1 (AT1) cell differentiation during alveolarization, homeostasis and injury repair (15,42,43,49,50).…”
Section: Loss Of Matrix Fibroblast Function Results In At2 Hyperplasi...mentioning
confidence: 99%
“…PDGFRA + fibroblasts support alveolar type 2 (AT2) and alveolar type 1 (AT1) cell differentiation during alveolarization, homeostasis and injury repair (15, 42, 43, 49, 50). Immunohistochemistry for the AT2 cell marker proSPC and AT1 cell markers HOPX and AGER were performed on control and GATA6 PDGFRAΔ/Δ lungs at PN7 and PN28 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Wnt5a expression has been shown to be induced during AEC2-to-AEC1 differentiation in vitro upon treatment with IGF-I (insulin-like growth factor 1) ( 16 ). Moreover, in vivo studies have shown that loss of function of Wnt5a impairs AEC1 differentiation ( 15 ), while gain of function of WNT5a promotes AEC2-to-AEC1 differentiation ( 17 ). The latter study also showed that WNT5A inhibits canonical WNT signaling in a subset of AEC2s defined by low expression of Sftpc (surfactant protein C) ( 17 ).…”
mentioning
confidence: 99%